RELATIONSHIP BETWEEN SCREEN TIME AMONG CHILDREN WITH NUTRITIONAL STATUS AND THEIR DEVELOPMENT - Siska Nawang Ayunda Maqfiro; Irmasanti Fajrin; Nurkila Suaib (Midwifery and Nursing Research, 2021)
Background: The growth and development of children are two events that are different in nature but are related to one another. It is possible for people in downtown areas to experience easy internet access, so that everything cannot be separated from digital media. Especially during the COVID-19 pandemic like today, where children have to stay at home more, besides that learning is also done from home, so the screen time has increased. The goals of the research is to analyze the relationship between screen time among children with nutritional status and their development.Methods: The research design used cross sectional analysis. The population is all children aged 3-5 years in Kalumpang Village in November 2020 as many as 497 children, the number of samples is 84 children using purposive sampling technique.Results: Based on the spearman-rank statistical test, it is known that p-value = 0.002 (p-value α), which with the correlation coefficient (r) = 0.330 that the relationship between Screen time with nutritional status is in the low category and has a positive relationship direction, namely the higher the screen time, the higher the nutritional status. Meanwhile, based on the spearman-rank statistical test, it is known that p-value = 0.001 (p-value α), with the correlation coefficient (r) = 0.371 that the relationship between Screen time with development is in the low category and has a positive relationship direction, namely the higher the screen time, the development will deviate from age.Conclusion: There is a relationship between screen time and nutritional status and  there is a relationship between screen time and children development. So it is very important to improve parental control behavior towards the use of electronic devices in children aged 3-5 years old.